Reduced Fragmentation of IGFBP-2 and IGFBP-3 as a Potential Mechanism for Decreased Ratio of IGF-II to IGFBPs in Cerebrospinal Fluid in Response to Repeated Intrathecal Administration of Triamcinolone Acetonide in Patients With Multiple Sclerosis - Hoeflich, Andreas; Fitzner, Brit; Walz, Christina; Hecker, Michael; Tuchscherer, Armin; Brenmoehl, Julia; Zettl, Uwe Klaus (Frontiers in Endocrinology, 2021)
Multiple sclerosis (MS) is a chronic autoimmune disease of the brain and spinal cord causing a wide range of symptoms such as impaired walking capability, spasticity, fatigue, and pain. The insulin-like growth factor (IGF) system has regulatory functions for the induction of inflammatory pathways in experimental encephalomyelitis. We have therefore assessed expression and regulation of the IGF system on the level of IGFs and IGFBPs in serum and cerebrospinal fluid (CSF) in the course of four repeated triamcinolone acetonide (TCA) administrations in two female and four male MS patients. Sample series of 20 treatment cycles were analyzed. IGF-1 and IGF-2 were quantified by ELISAs, and IGFBPs were analyzed by quantitative Western ligand (qWLB) and Western immunoblotting (WIB) in order to differentiate intact and fragmented IGFBPs. The ratios of fragmented to intact IGFBP-2 and -3 were calculated in serum and CSF. Finally, the ratios of IGF-1 and IGF-2 to the total IGF-binding activity, quantified by qWLB, were determined as an indicator of IGF-related bioactivity. After the fourth TCA administration, the average level of IGF-1 was increased in serum (p<0.001). The increase of IGF-1 concentrations in serum resulted in an increased ratio of IGF-1 to IGFBPs in the circulation. By contrast in CSF, fragmentation of IGFBP-2 and IGFBP-3 and the ratio of IGF-2 to intact IGFBPs were decreased at the fourth TCA administration (p<0.01). Furthermore, reduced fragmentation of IGFBP-3 in CSF was accompanied by increased concentrations of IGFBP-3 (p<0.001). We conclude that reduced fragmentation of IGFBPs and concomitant reduction of IGF-2 to IGFBP ratios indicate regulation of bioactivity of IGF-2 in CSF during repeated intrathecal TCA administration in MS patients.